Avaliação das propriedades macro e microestruturais de ligantes a base de escória ativados por carbonatação acelerada - Weide, Heliton (2024)
Recent studies evaluate accelerated carbonation as an alternative to produce special binders from steel production slags activated by CO2. The use of industrial waste to manufacture commercially valuable materials aligns with the industry's interest in circular economy and carbon sequestration. This study aimed to evaluate the accelerated activation process of electric arc furnace (EAF) slag by CO2, with the goal of obtaining a clinker-free binder. Cylindrical test specimens (CPs) with a diameter of 2 cm and a height of 3.5 cm were molded, using a mass ratio of 1:3, consisting of EAF slag and sand with four different particle sizes (1.2 mm, 0.6 mm, 0.30 mm, and 0.15 mm). The water/dry material ratio was 7%. The samples underwent accelerated carbonation under varying conditions of temperature (40, 60, and 80 °C), CO2 pressure (5, 10, 40, and 60 bar), and carbonation times (2, 4, and 6 hours). Control samples, without the CO2 activation process, were also prepared. Both activated and control samples were stored in a climate-controlled room and then subjected to compression strength tests. The control samples were tested at 7, 28, 91, and 180 days, while the activated samples were tested at 7 days. To understand the influence of the tested factors, statistical analysis using ANOVA was applied, complemented by Tukey’s post hoc test, with a significance level of 95%. After the compression tests, fragments of the specimens were collected for microstructural analyses, using techniques such as X-ray diffraction (XRD), scanning electron microscopy (SEM), and Fourier-transform infrared spectroscopy (FTIR). The statistical results indicated that carbonation time was a significant factor for all temperatures studied. Additionally, at 60 °C, pressure also showed a significant influence. The optimal configuration for the carbonation process of EAF slag was determined to be 60 °C, 5 bar of CO2 pressure, and 6 hours of exposure, achieving a compressive strength of 12.16 MPa. This value represented an increase of approximately 1154% compared to the maximum strength obtained by the reference samples, which was 0.97 MPa. XRD analysis identified the formation of phases such as calcite, magnesian calcite, and humboldtine after the carbonation process. Thermogravimetric analysis (TG/DTG) identified mass loss in characteristic ranges of carbonated phases, which was confirmed by the identification of C-O vibrational groups in the FTIR analysis. The morphology of the samples observed by SEM revealed that the increased carbonation time contributed to the densification of carbonation products in the paste/sand transition zone, near the fracture zone. The activation process of EAF slag by CO2 proved to be efficient in increasing compressive strength in less time compared to non-activated samples. Additionally, it contributed to the sequestration and fixation of CO2, representing an alternative with lower environmental impact compared to Portland cement.